KEARIFAN LOKAL PESANGGERAHAN GEMBIROWATI SEBAGAI SUMBER BELAJAR KEANEKARAGAMAN JENIS VEGETASI STRATA POHON - Handayani, Trikinasih; Alpendi, Alpendi; Utamie, Listiatie Budi; Permatasari, Indah (BIOEDUKASI (Jurnal Pendidikan Biologi), 2024)
This research aims to determine the types of tree strata vegetation, calculate the Importance Value Index and Diversity Index in Pesanggerahan Gembirowati, and the relationship between abiotic environmental conditions (air temperature, air humidity, soil temperature, soil moisture, pH, and light intensity) on stand grouping patterns, The potential for research results as a source of biology learning in biological material is high. This research is exploratory. Data collection uses Point Centered Quarter. The diversity index uses Shannon-Wienner and the correlation of measured abiotic environmental conditions (air temperature, air humidity, soil temperature, soil water content, pH, and light intensity) with stand grouping patterns using the SPSS 20 cluster program. Potential learning resources are carried out by descriptive assessment. The research results showed that there were 20 types of tree strata. The highest INP was Cocos nucifera L. (50.0%) and the lowest INP was Muntingia calabura L. (2.9%). The tree strata diversity index is classified as moderate, ranging from 1.09 to 1.19. Abiotic environmental conditions are interrelated and withstand grouping patterns. The research results have the potential to be a source of Biology learning in high school.